GE_GERICHTE C/6697/2012 vom 22. November 2013 - GE Cour de justice (2013)
DIVORCE; VALEUR LITIGIEUSE; MAXIME DU PROCÈS; NOUVEAU MOYEN DE FAIT; OBLIGATION D'ENTRETIEN; REVENU HYPOTHÉTIQUE; ENFANT | CC.276; CC.285